Free-swimming tests for the aerobic and anaerobic quality assessment: a scoping review of the last ten years studies - Demarie, S.; Fagnani, F.; Guidotti, F. (Medicina dello Sport, 2024)
INTRODUCTION: Swimming kinematics cannot be expressed other than in free swimming, consequently, to estimate the swimmers physiological and technical qualities, field tests should be the most appropriate. The aim of the study is to provide evidence-based information on the most used and most related to performance free swimming tests for the aerobic and anaerobic swimmer`s quality assessment.